2020
DOI: 10.1007/s00415-020-10043-x
|View full text |Cite
|
Sign up to set email alerts
|

The DizzyQuest: to have or not to have… a vertigo attack?

Abstract: Background The DizzyQuest, an app-based vestibular diary, provides the opportunity to capture the number and nature of vertigo attacks in daily life. To accomplish this, the DizzyQuest provides different strategies: event sampling using an attack questionnaire, and time sampling using an evening questionnaire. Objective of this study was to investigate whether the number and nature of reported vertigo attacks was comparable between the two questionnaires. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Most likely due to recall bias, episodes of fluctuations in hearing loss were overreported at time of inclusion. This is also congruent with a previous study with the DizzyQuest, in which the reported frequency of vertigo attacks was much higher in a retrospective end of day questionnaire than in the questionnaires which needed to be completed right after a vertigo attack [ 26 ]. The lack of PTA variability might have underestimated the relationship between PTA and self-reported hearing loss and tinnitus severity, as a result of the “restriction of range effect”.…”
Section: Discussionsupporting
confidence: 91%
“…Most likely due to recall bias, episodes of fluctuations in hearing loss were overreported at time of inclusion. This is also congruent with a previous study with the DizzyQuest, in which the reported frequency of vertigo attacks was much higher in a retrospective end of day questionnaire than in the questionnaires which needed to be completed right after a vertigo attack [ 26 ]. The lack of PTA variability might have underestimated the relationship between PTA and self-reported hearing loss and tinnitus severity, as a result of the “restriction of range effect”.…”
Section: Discussionsupporting
confidence: 91%
“…This interesting finding was outside the scope of this article, since it mainly results from the differences between reporting strategies: event sampling (attack-questionnaire) and time sampling (evening-questionnaire). This will therefore be discussed separately [52].…”
Section: Frequency and Nature Of Attacks Of Vertigo Or Dizzinessmentioning
confidence: 99%